If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -1 = 3t + 7 Reorder the terms: -1 + 4t = 3t + 7 Reorder the terms: -1 + 4t = 7 + 3t Solving -1 + 4t = 7 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. -1 + 4t + -3t = 7 + 3t + -3t Combine like terms: 4t + -3t = 1t -1 + 1t = 7 + 3t + -3t Combine like terms: 3t + -3t = 0 -1 + 1t = 7 + 0 -1 + 1t = 7 Add '1' to each side of the equation. -1 + 1 + 1t = 7 + 1 Combine like terms: -1 + 1 = 0 0 + 1t = 7 + 1 1t = 7 + 1 Combine like terms: 7 + 1 = 8 1t = 8 Divide each side by '1'. t = 8 Simplifying t = 8
| x^2-16=2x^2-14x+21 | | 4x+5=10x-23 | | -.75n+7=25 | | 3-.2x=.3x-7 | | 5x-6=1-2x | | (a+3b)x+(a+3b)y= | | 8b+3b-6=38 | | 0.6666666666x-4=10 | | -2x+8=-6+5 | | -2(-10)-y=16 | | x+y=630 | | 6s-2=5s+10 | | 12-.6x=-27 | | (16x+5y)dx+(3x+y)dy=0 | | x*x=-36 | | 2x^3-8x^2-14x= | | 10x=4.09 | | n^3-n-3360=0 | | e^1-7x=9 | | (6-v)(3v-4)=0 | | x=2600 | | x-.2=13000 | | x*x=5 | | 4x+1=25-2x | | 15o^2+36o+17=0 | | ln(3x)=5.82 | | y^2+-3y+-40=0 | | 4.9(x+5.1)=36.8 | | -6n=54 | | -9+n=-8 | | 11x-2=3x+11 | | o^2+0o+-4=0 |